TO THEORY OF MAGNETIC FLUID SEAL - V. G. Bashtovoi; A. M. Algadal (Наука и техника, 2006)
A theoretical model of magnetic fluid seal is proposed and it permits to carry out calculation of its static characteristics while using analytical methods. Comparison of theoretical and experimental results shows an adequacy of the proposed model to the actual situation.